POLA PENGOBATAN PASIEN SCHIZOPRENIA PROGRAM RUJUK BALIK DI PUSKESMAS MUNGKID PERIODE JANUARI-JUNI 2014 - Hariyani, Hariyani; Astuti, Fitriana Yulia; Kusuma, Tiara Mega (Universitas Ahmad Dahlan, 2016)
Schizoprenia is one of psychiatric disorders that caused by brain damage. One of schizoprenia handling is giving antipsychotics to prevent the symptoms, that antipsychotics was effective therapy to treat it. This study aims to determine the treatment pattern of schizoprenia patient behind reconciliation program at Puskesmas Mungkid. The method used is analytical survey with retrospective data collection. This research were conducted on 42 medical records of patients in period January-June 2014 which receive antipsychotics medication and were analyzed with descriptive analysis. Obtained data of this research, showed that the most common single therapy of for antipsychotics is haloperidol (54,93%) and the most common therapy was haloperidol and chlopromazine (61,91%). The most common treatment category of schizoprenia is the typical antipsychotic treatmemt (92,96%), while for appropriate dose and the use of antipsychotic drugs were used 97,18% and 2,82% were not appropriate to the standar.